2014
DOI: 10.1155/2014/628712
|View full text |Cite
|
Sign up to set email alerts
|

Yiqi Formula Enhances the Antitumor Effects of Erlotinib for Treatment of Triple‐Negative Breast Cancer Xenografts

Abstract: Yiqi formula (YF), a traditional herbal prescription, has long been used to treat triple-negative breast cancer (TNBC) patients. The present study aims to investigate the effects and the related mechanism of YF for treatment of TNBC xenografts. MDA-MB-231 (human TNBC) cells were subcutaneously injected into the second mammary fat pad of 40 female nude mice, which were divided into four groups: control, erlotinib (an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor), YF, and combination (YF plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated the superior effect of erlotinib (EB) on EGFR signaling pathway blocking, which results in an obvious inhibition effect of tumor cells growth, invasion and migration (Liu et al., 2017). Additionally, treating with EB also played a promoting role in accelerating cell apoptosis and disruption of angiogenesis through inhibition of the cell cycle protein kinase dependent inhibition protein p27 (p27kip1 protein) (Liao et al., 2014). In the present study, therefore, we have developed PLA-based nano-platforms and used EB as a model drug to treat TNBCs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the superior effect of erlotinib (EB) on EGFR signaling pathway blocking, which results in an obvious inhibition effect of tumor cells growth, invasion and migration (Liu et al., 2017). Additionally, treating with EB also played a promoting role in accelerating cell apoptosis and disruption of angiogenesis through inhibition of the cell cycle protein kinase dependent inhibition protein p27 (p27kip1 protein) (Liao et al., 2014). In the present study, therefore, we have developed PLA-based nano-platforms and used EB as a model drug to treat TNBCs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wenshen Zhuanggu formula mitigates breast cancer bone metastasis through suppression of Jagged1/Notch and TGF-β1/Smads pathway [ 5 , 20 ]. Yiqi formula inhibited the TNBC xenograft tumor growth by reducing p-EGFR and p-AKT1 [ 21 ]. Therefore, deeply understanding the mechanisms of CHM in tumor progression may provide new perspectives for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%